"Be Realistic. Hope for a Miracle": On the Coexistence of Grief and Optimism Among Caregivers of Patients With Prolonged Disorders of Consciousness. (April 2022) - Yehene, Einat; Neeman, Yasmin; Zaksh, Yael; Elyashiv, Maya
This cross-sectional study explored caregivers' views on patient prognosis, alongside dispositional optimism and grief in prolonged disorders of consciousness. Participants were 64 primary family caregivers (aged 34–80 years) of patients diagnosed with either persistent vegetative state or minimal conscious state, all hospitalized in a long-term medical–rehabilitative institute. Caregivers' views on prognosis were derived from questions designed to assess belief in improvement (Question 1) and medical prospect 5 years forward (Question 2). Grief was assessed using selected scales from the Two-Track Bereavement Questionnaire and dispositional optimism by the Life Orientation Test-Revised . While caregivers' optimism was significantly higher than the normative population, their grief levels resembled death. Classification based on belief in improvement (Question 1) indicated that despite an equivalent time since injury, caregivers conveying a positive prognosis exhibited intensified grief and were more optimistic, religious, and patient-oriented, relative to those conveying a negative prognosis. Our findings point to caregivers' utilization of optimism and highlight the importance of seeing hope as a dynamic process in such continuous medical states of uncertainty. Thus, clinical interventions should be attuned to the role dispositional versus unrealistic optimism plays in caregivers' hope-related goal setting, while working through mitigating their grief.